A prospective study regarding cardiovascular manifestations following snake bite - M. S., Anitha; Nandimath, Viresh A.; Bandichhode, Sachin T. (International Journal of Advances in Medicine, 2017)
Background: Snake bite is an occupational hazard especially of agricultural workers. Through snake bite venom, a complex mixture of various enzymes, polypeptides and toxins are injected into body of the victim. Clinical features of snake bite include local effects such as pain, swelling, cellulitis, tissue necrosis and lymphadenopathy. Snake bite and its common complications like nephrotoxicity, neurotoxicity and haemorrhagic manifestations have always been stressed. The cardiovascular abnormalities following snake bite was relatively less stressed complication; hence the present study has been conducted. Aim of the study was to observe clinical, electrocardiographic and cardiac changes following snake bite. Methods: Present prospective study has been conducted in emergency ward of medicine department of K. R. Hospital, Mysore, India during the period from July 2004 to May 2005. Results: In the present study 80% of cases were in second and third decade of life. Male patients were outnumbered female patients. 70% of cases were from agricultural background. Distal part of the body was the most common site involved in snake bite, 82% of cases presented within 24 hours of snake bite. Cardiac manifestations were seen in 36% of cases in the form of hypotension, ECG changes and elevated cardiac enzymes. Conclusions: Cardiovascular system involvement following snake bite was not rare, it was mandatory to record ECG and estimate cardiac enzymes as soon as possible in detecting cardiotoxic effects following snake bite.